ANTIFUNGAL ACTIVITY OF RAMANIA LEAF EXTRACT (Bouea Macrophylla Griff) AGAINST Candida albicans - Reski Nurafia; Isyana Erlita; Yusrinie Wasiaturrahmah (FKG Unlam, 2023)
Background: Root canal infection is a polymicrobial infection that causes pulpitis or localized pulp inflammation. Root canal infection occurs due to the presence of pathogenic microorganisms in the root canal. One of the most common pathogenic microorganisms found in root canals is the fungus Candida albicans. Treatment that can be done to treat pulp tissue infection is endodontic treatment. Chlorhexidine gluconate 2% is one of the irrigation materials that can be used in root canal treatment. Ramania leaf extract contains compounds such as triterpenoids, phenols, flavonoids, steroids, saponins, alkaloids, and tannins that can function as antifungals. Purpose: Measuring and analyzing the antifungal activity of ramania leaf extract (Bouea Macrophylla Griff) on the growth of Candida albicans. Method: This study is a true experimental study with a post-test-only design with a control group design consisting of 7 treatment groups and repeated 4 times. The antifungal activity was assessed from the inhibition zone formed on Sabouraud Dextrose Agar media by the diffusion method. Results: Based on the Mann-Whitney test showed that there was only 1 pair of groups that did not have a significant difference, namely 100% concentration of ramania leaf extract with 2% chlorhexidine gluconate while the other groups had significant differences from each other. Conclusion: Ramania leaf extract concentrations of 6.25%, 12.5%, 25%, 50%, and 100% had antifungal activity in inhibiting the growth of the fungus Candida albicans. Keywords: Antifungal Activity, Candida albicans, Chlorhexidine gluconate 2%, Ramania Leaf Extract.